Establishment of plastic-associated microbial community from superworm gut microbiome - Liu, Yinan (2024)
Gut microbial communities of plastic-munching worms provide novel insights for the development of plastic-processing biotechnologies. Considering the complexity of worm maintenance and the gut microbial communities, it is challenging to apply the worms directly in plastic processing. Harnessing the power of microbial communities derived from the worm gut microbiomes in vitro may enable a promising bioprocess for plastic degradation. Here, we established stable and reproducible plastic-associated biofilm communities derived from the gut microbiome of a superworm, Zophobas atratus, through a two-stage enrichment process: feeding with plastics (HDPE, PP, and PS) and in vitro incubation of gut microbiomes obtained from the plastic-fed worms. Plastic feeding exhibited marginal influence on bacterial diversity but substantially changed the relative abundance of different bacterial groups, and intriguingly, enriched potential plastic degraders. More prominent shifts of microbial communities were observed during the in vitro incubation of the gut microbiomes. Taxa containing plastic-degrading strains were further enriched, while other taxa represented by lactic acid bacteria were depleted. Additionally, the plastic characterization confirmed the degradation of the incubated plastics by the plastic-associated microbial communities. Community functional inference for both gene abundance and community phenotype suggested that the in vitro incubation enhanced plastic-degrading potential. Deterministic ecological effects, in particular, selection processes, were identified as the main driving force of the observed community shifts. Our findings provide novel insights into plastic-munching-worm-inspired bioprocessing of plastic wastes.